Hypothalamic hamartoma presenting as central precocious puberty in a girl: a case report - Mohanty, Soumya Ranjan (International Journal of Contemporary Pediatrics, 2025)
Central precocious puberty (CPP) is defined as the early onset of secondary sexual characteristics due to premature activation of the hypothalamic pituitary gonadal (HPG) axis. Hypothalamic hamartomas are rare but classical causes of CPP. We report a case of a 2 years 7 months old girl with progressive breast enlargement and pubic hair development, found to have a hypothalamic hamartoma on MRI.